2021
DOI: 10.15581/004.41.002
|View full text |Cite
|
Sign up to set email alerts
|

Pre-service teachers’ perceptions and training contributions towards ICT use

Abstract: Previous studies have concluded that ICT are underused in primary and early childhood classrooms partly due to lack of appropriate training. This study explores ICT use and the validity of a training proposal as reported on a survey by two groups of students after their teaching practicum. Results showed traditional technological tools were used more frequently than collaborative tools and suggest that receiving an instructional technology course provided students with a broader toolkit of ICT tools, a more cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 0 publications
2
10
0
Order By: Relevance
“…This pattern of training impacted negatively on teachers' use of IWBs in pedagogy, as more focus was on technology. These findings confirm previous studies indicating that poor training leads to no usage, or under-usage of ICT technology within a teaching and learning environment [31].…”
Section: Discussionsupporting
confidence: 91%
“…This pattern of training impacted negatively on teachers' use of IWBs in pedagogy, as more focus was on technology. These findings confirm previous studies indicating that poor training leads to no usage, or under-usage of ICT technology within a teaching and learning environment [31].…”
Section: Discussionsupporting
confidence: 91%
“…The next trend of research may be predicted to move toward creating teacher training programs that prepare students for their professional responsibilities by enhancing their digital literacy. One such effort has been reported by Bueno‐Alastuey and Villarreal (2021).…”
Section: Discussionmentioning
confidence: 99%
“…As the few reported experiences of meaningful situated professional development focused on material design among pre-service teachers have been shown to be successful (Banegas et al, 2020;Bueno-Alastuey & Villarreal, 2021;Gil-Flores et al, 2017;Kuru Gönen, 2019Gil-Flores et al, 2017;Kuru Gönen, 2019), this case study explores whether combining university training with material design and real-life practices can help foster CLIL skills and ICT integration at the same time.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Both a lack of appropriate quality CLIL resources (Ball et al, 2015;Banegas, 2016;Lasagabaster & Doiz, 2016) and insufficient knowledge to integrate ICT in teaching and learning processes to promote enhanced learning experiences (Blackwell et al, 2014) have consistently been reported as major obstacles for effective CLIL programme implementation. Furthermore, a reported shortage of meaningful and practical professional development for pre-service teachers (Bueno-Alastuey & Villarreal, 2021;Gil-Flores et al, 2017) has contributed to aggravating this situation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation